Effect of Various Electrolytes on Theophylline Loaded Sodium Alginate Beads Prepared by Ionic Cross Linking Technique (Dhaka University Journal of Pharmaceutical Sciences, 2013)
The purpose of t h e present research work was to prepare alginate beads containing water soluble drug theophylline using ionic cross linking technique, with electrolyte type and concentration as variables. In this study, the beads were characterized and evaluated in respect of their surface morphology, swelling index and in vitro kinetics. The comparative study among the three polyvalent cationic cross linking agents CaCl2 , BaCl2 and Al2 (SO4)3 were investigated based on their cationic charges. Divalent cation, Ca2+ and Ba2+ containing beads showed simultaneous decrease in drug release with increasing electrolyte amount. In case of Al3+ -alginate beads, the delay in release was due to the ability of Al3+ to form three dimensional bonding structure with the sodium alginate inside the beads. As a result, swelling of beads is delayed leading to slow disintegration. Scanning electron microscope (SEM) photomicrographs revealed that with the increase in the electrolyte concentration the density of the cross link is also increased. When the electrolyte concentration is 5 % then the beads surface is rough and rod shape drug is visible. But when the electrolyte concentration is increased from 10 % to 15 % the surface is comparatively smoother and both the swelling property and in vitro drug release are decreased. Most of the formulations followed Higuchi drug release model. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14578 Dhaka Univ. J. Pharm. Sci. 11(2): 181-189, 2012 (December)